Factors Affecting Profitability (Study On State-Owned Banks In Indonesia) - Priharta, Andry; Gani, Nur Asni; Harun, Siti Hafnidar (GOVERNORS, 2024)
The research aims to determine the effect of Capital Adequacy Ratio, Non-Performing Loans, Loan to Deposit Ratio and Net Interest Margin on profitability as measured by ROA. The study was conducted at banks owned by the Government of the Republic of Indonesia or known as Bank BUMN (State-Owned Enterprises) which consists of four banks, namely Bank Mandiri (Bank Mandiri), Bank Rakyat Indonesia (BRI), Bank Negara Indonesia (BNI) and Bank Tabungan Negara (BTN). The method of the research was quantitative research, analysis secondary data. It was conducted from the financial reporting Bank BUMN period from 2011 to 2022. By multiple linear regression analysis, it was found that CAR has a significant negative effect, NPL has a significant negative effect, LDR has a significant positive effect, and NIM has a significant positive effect on profitability. Furthermore, the coefficient of determination shows that the model is able to explain 84.90% of the variation in the four dependent variables.